γδ T cell frequencies are altered in HIV positive pregnant South African women and are associated with preterm birth - Akoto, C; Chan, CYS; Ravi, K; Zhang, W; Vatish, M; Norris, SA; Hemelaar, J (Public Library of Science, 2020)
Background Preterm birth is the leading cause of neonatal and child mortality worldwide. Maternal HIV infection and antiretroviral treatment (ART) increase the rate of preterm birth, but the underlying mechanisms remain unknown, limiting progress in prediction, prevention and treatment. While overall γδ T cell levels remain constant, acute HIV infection is associated with a depletion of the Vδ2 subset and an increase in the Vδ1 subset, which do not return to baseline with ART. γδ T cells have also been implicated in adverse pregnancy outcomes and we therefore investigated the potential association between maternal HIV infection, peripheral γδ T cell frequencies and preterm birth. Methods Study participants were HIV positive (n = 47) and HIV negative (n = 45) women enrolled in a prospective pregnancy cohort study at Chris Hani Baragwanath Academic Hospital in Soweto, South Africa. Women were enrolled in early pregnancy and gestational age was accurately determined by first trimester ultrasound scan. Peripheral blood samples were collected in each trimester and peripheral blood mononuclear cells isolated. Frequencies of γδ T cells, Vδ1+ and Vδ2+ γδ T cell subsets, and CCR6 chemokine receptor expression were determined by flow cytometry. Results Total γδ T cell levels were similar between HIV positive and HIV negative women throughout pregnancy. However, in each trimester maternal HIV infection was associated with reduced levels of the Vδ2+ subset and increased levels of the Vδ1+ subset, leading to a reversal of the Vδ1/Vδ2 ratio. Timing of ART initiation among HIV positive women did not affect levels of γδ T cells, the Vδ1+ and Vδ2+ subsets, or the Vδ1/Vδ2 ratio. Importantly, preterm birth was associated with lower total γδ T cell levels in early pregnancy and γδ T cell frequencies were lowest in HIV positive women who delivered preterm. Moreover, in the first trimester the proportion of Vδ1+ T cells that were CCR6+ was significantly reduced in HIV+ women and women who delivered preterm, resulting in the lowest proportion of CCR6+ Vδ1 T cells in HIV positive women who delivered preterm. Conclusions Our findings suggest that altered γδ T cell frequencies may link maternal HIV infection and preterm birth. γδ T cell frequencies in early pregnancy may serve as predictive biomarkers to identify women at risk of delivering preterm.